Ligation assisted endoscopic mucosal resection of neuroendocrine tumor of duodenal bulb: a case report with a follow up of 24 months - Shestha, Umid Kumar; Aryal, Gopi (Journal of Advances in Internal Medicine, 2019)
Duodenal neuroendocrine tumor (NET) is a rare solitary lesion arising from the mucosa and submucosa of the duodenum, which is found incidentally during upper gastrointestinal endoscopy. Eendoscopic Mucosal Resection (EMR) has been the commonly used endoscopic procedure for duodenal carcinoid tumors, but the conventional EMR done to resect duodenal NET s is likely to have positive vertical margins. However, the ligation assisted EMR has recently been shown to be a promising technique for the treatment of duodenal NET that can have a negative free margin. In our study, we present a patient of 51-year-old male, who presented with pain over epigastrium and upper gastrointestinal endoscopy revealed a small submucosal lesion of 10 mm in the duodenal bulb. The endoscopic ultrasound showed the lesion arising from the echo layer three. The biopsy was taken which showed the duodenal NET. The computed tomography of abdomen did not show any evidence of distant metastasis. The EMR of duodenal NET was done by band ligation technique. The biopsy from the resected duodenal lesion confirmed the duodenal NET with the margin free of the tumor. The patient was followed at 6, 12, 18 and 24 months. During the follow up visits, the repeat upper gastrointestinal endoscopy did not show recurrence of the lesion and there was no any evidence of distant metastasis either. Ligation assisted EMR is an acceptable treatment in the hands of expert for small duodenal NET without the evidence of metastasis and can ensure the complete removal of the lesion with vertical free margin.